Continuous audit model: data integration framework - Mauricio Mello Codesso; Paulo Caetano da Silva; Miklos A. Vasarhelyi; Rogério João Lunkes (Revista Contemporânea de Contabilidade)
The approximation of business areas with the use of new technologies, real-time savings, transactions with several countries and on several continents with different law guarantees are necessary. These warranties can be acquired through Continuous Audit (CA). However, to be able to perform the analysis the auditors need to have access and extract the data. Previous researchers only emphasis on the benefits of applying the CA methods, but do not explain how to retrieve and organize the data.  The paper aims to contribute to the literature with the deepening of ways to access, structure and collect critical and necessary data for CA. With the deepening of Audit Data Standard and  XBRL, as well as creating a basis for future research with the integration of extraction, analysis, and exception detection algorithms that are used by CA.